INVESTIGASI ORIENTASI USAHA DAN PENGEMBANGAN MODEL PENGUATAN UNTUK USAHA KECIL DAN MENENGAH: SEBUAH KAJIAN EMPIRIK - Afifah Afifah; Gustina Gustina (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2016)
West Sumatra is a province which is possess a variety of traditional food. Such foods have became souveniricon for visitors who come to the tourist areas of West Sumatra. These kinds of food produced by Small andMedium Enterprises (SMEs) scattered throughout the territory of West Sumatra. Government group them intosnack cluster. The purpose of this study was to investigate the affirmation model of snack SMEs in WestSumatra as well as to arrange simulation of the models designed. This is qualitative study implements FocusGroup Discussion and in-depth interview as data collection method . The results show that snack SMEs in thesample region need to be reinforced through training, mentoring, and coaching. Training required includeentrepreneurial and managerial skills.